2010
DOI: 10.1007/s10856-010-4175-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an osteostimulative putty in the sheep spine

Abstract: The objective of this study is to evaluate local response to a bioactive glass based composite putty (NovaBone Putty) in a vertebral body defect model in sheep, as compared to NovaBone, a bioactive glass particulate. Two time periods were used for the study, 6 and 12 weeks. Empty defects were also used as a control. In comparing the three test groups, the relative amount of new bone for both grafted defects was substantially greater than for the empty controls (P < 0.05). At 6 weeks, the bone formation was 42%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 18 publications
3
22
0
Order By: Relevance
“…Both the test and the control samples were biocompatible and showed high new bone formation along with high vascularization and periosteal growth. With the BAG S53P4 putty, no indication of possible disturbed bone formation by the PEGglycerol binder was seen, which is in line with earlier studies [17,29]. We also found that the bioactive glass granules in the BAG S53P4 putty showed a slightly higher in-tramedullary ossification than the controls, but no difference in the cortical ossification was seen.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Both the test and the control samples were biocompatible and showed high new bone formation along with high vascularization and periosteal growth. With the BAG S53P4 putty, no indication of possible disturbed bone formation by the PEGglycerol binder was seen, which is in line with earlier studies [17,29]. We also found that the bioactive glass granules in the BAG S53P4 putty showed a slightly higher in-tramedullary ossification than the controls, but no difference in the cortical ossification was seen.…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings at 6 and 12 weeks after surgery with NovaBone putty have been shown revealing a greater bone content in the putty group than in the particulate group [29]. As stated by Wang et al, a possible explanation for the increased bone formation with the putty material could be that addition of the carrier maintains a better spatial distribution of the particles [29]. Altogether, the novel BAG S53P4 putty can be considered to be biocompatible and non-toxic as earlier demonstrated for BAG in general [33].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations